Blockade of osteopontin reduces alloreactive CD8(+) T cell–mediated graft-versus-host disease - Zhao, Fang (American Society of Hematology, 2011)
Graft-versus-host disease (GVHD), a life-threatening complication after allogeneic hematopoietic stem cell transplantation, is caused by alloreactive donor T cells that trigger host tissue damage. The inflammatory environment inside recipients is critical for GVHD pathogenesis, but the underpinning mechanisms remain elusive. Using mouse model of human GVHD, we demonstrate osteopontin (OPN), a potent proinflammatory cytokine, plays an important role in regulating activation, migration, and survival of alloreactive T cells during GVHD. OPN was significantly elevated after irradiation and persisted throughout the course of GVHD. Blockade of OPN attenuated GVHD with reduced accumulation of donor T cells in recipient organs. Amelioration was the result of migration and survival suppression caused by anti-OPN treatment on donor-derived T cells for 2 reasons. First, OPN promoted the migration and infiltration of naive and alloreactive CD8(+) T cells into host organs. Second, it also facilitated activation and viability of donor-derived CD8(+) T cells via synergizing with T-cell receptor/CD3 signaling. Finally, anti-OPN treatment retained graft-versus-leukemia effect of alloreactive CD8(+) T cells. This study demonstrates, to our knowledge for the first time, the critical effect of OPN in the initiation and persistence of CD8(+) T cell-mediated GVHD and validates OPN as a potential target in GVHD prevention.